Implementation of Joyful Learning through Number Based Unplugged Coding to Enhance Kindergarten Children's Creativity - Muvita, Nunung Ari; Wardhani, Junita Dwi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to implement a joyful learning strategy through number based unplugged coding activities to enhance early childhood creativity, as well as to identify obstacles during implementation and the adaptive strategies used by teachers.Methodology: The study employed a qualitative case study approach at Aisyiyah Bustanul Athfal I Ngadirojo Kindergarten, Wonogiri, involving 20 children aged 5–6 years. Data were collected through observation, semi structured interviews, and documentation, and analyzed using the Miles and Huberman interactive model with triangulation to ensure validity.Results: The implementation of joyful learning through number-based unplugged coding effectively improved children's creativity across four indicators: fluency, flexibility, originality, and elaboration. Children demonstrated increased initiative in generating movement patterns, modifying task sequences, and creating unique variations supported by storytelling. The average creativity score increased by +1.14 points, indicating notable development. Challenges included variations in number/color recognition, differences in motor skills, classroom management during heightened enthusiasm, and limited time. These were addressed through gradual scaffolding, multisensory learning media, small group organization, and time adjustments.Application/Originality/Value: The study provides a practical, low-cost, and developmentally appropriate model for integrating joyful learning with unplugged coding to stimulate creativity and support foundational computational thinking in early childhood learning environments.